A novel ventilation method to prevent obstruction phenomenon within sewer networks. (March 2022) - Adouni, Hella; Chouari, Yoldoss; Bournot, Hervé; Kriaa, Wassim; Mhiri, Hatem
Highlights: Effect of air velocity on the behavior of the air-water interface. Critical air velocity causing the obstruction of the channel is defined. Parametric study of the injectors introduced in horizontal confined channel to avoid the obstruction. Effect of the Side-by-side inclined parietal jets installed along the entire length of the channel on the blocking phenomenon. Abstract: The phenomenon of blockage is a widely encountered issue in industrial applications with multiphase flows such as sewer networks. This paper proposes a solution to eliminate the blocking phenomenon in such confined horizontal channels. The study presents alternative longitudinal ventilation using inclined jets. Numerical simulations were performed to evaluate several parameters such as the position of the jets, their orientation and the velocity ratio between the main air inlet and the jets. The Volume of Fluid model (VOF) is used to follow the evolution of the interface between the air and water phases. Numerical results of the axial velocity were confronted to the experimental data obtained by the Laser Doppler Anemometry (LDA) technique and gave good agreement. The parametric study shows that the lateral injection has a direct effect on the dynamic of the air-water flow inside channels. With the optimal depicted position and orientation of the injectors, the obstruction is avoided for low air velocities and is moved away from the entrance for the higher ones. Results show also that side-by-side lateral injection all over the channel with an optimal ventilation ratio fully avoid the occurrence of slug flow and thus the obstruction of the channel. Graphical abstract: Image, graphical abstract